Risk of Pleural Empyema in Adult Patients With Asthma: A Nationwide Retrospective Cohort Study - Liao, Wei-Chih; Lin, Cheng-Li; Shen, Te-Chun; Tu, Chih-Yen; Hsia, Te-Chun; Hsu, Wu-Huei (Frontiers in Medicine, 2022)
Background: Respiratory system infections are prevalent in patients with asthma. However, whether patients with asthma are at an increased risk of developing pleural empyema remains unclear. Methods: We conducted a retrospective cohort study using data from the National Health Insurance Research Database of Taiwan. The asthma cohort included 62,893 newly diagnosed adult patients between 2000 and 2012. The comparison cohort included the same number of individuals without asthma, frequency-matched for age, gender, comorbidity, and the year of diagnosis. The development of pleural empyema was monitored until the end of 2013. Results: The overall incidence of pleural empyema was 1.59-fold higher in the asthma cohort than in the comparison cohort (5.45 versus 3.42 per 10,000 person-years), with an adjusted hazard ratio (HR) of 1.62 (95% confidence interval [CI] = 1.34–1.97). Stratified analyses by age, gender, and comorbidity revealed that the crude and adjusted HRs of pleural empyema associated with asthma were all significant. Among patients with asthma, the risk of pleural empyema elevated with increased annual number of emergency room visits and hospital admissions (≥1 vs. <1, aHR = 11.6, 95% CI = 5.45–24.8 and aHR = 15.4, 95% CI = 8.80–27.1). Conclusion: An increased risk of developing pleural empyema is observed in adult patients with asthma than those without asthma. Furthermore, the risk of pleural empyema may increase with poor control of asthma.